2015
DOI: 10.1146/annurev-med-010714-112311
|View full text |Cite
|
Sign up to set email alerts
|

H7N9: Preparing for the Unexpected in Influenza

Abstract: In the years prior to 2013, avian influenza A H7 viruses were a cause of significant poultry mortality; however, human illness was generally mild. In March 2013, a novel influenza A(H7N9) virus emerged in China as an unexpected cause of severe human illness with 36% mortality. Chinese and other public health officials responded quickly, characterizing the virus and identifying more than 400 cases through use of new technologies and surveillance tools made possible by past preparedness and response efforts. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 35 publications
2
52
1
Order By: Relevance
“…Avian influenza refers to the infection of birds with avian influenza type A viruses [1]. These viruses occur naturally among wild aquatic birds worldwide and can infect over 100 domestic sources of poultry as well as other birds and animal species [2,3,4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Avian influenza refers to the infection of birds with avian influenza type A viruses [1]. These viruses occur naturally among wild aquatic birds worldwide and can infect over 100 domestic sources of poultry as well as other birds and animal species [2,3,4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Given the significant global improvements in laboratory characterization and surveillance, additional novel avian viruses are likely to be identified. Following the appearance of the H5N1virus in 1997, ongoing surveillance efforts have already improved not only the detection of the H7N9 (in 2013), H10N8 (in 2013) and H5N6 subtypes (in 2014), which have all caused severe infections, but also the detection of other subtypes such as H6N1, H7N2, H7N3, H7N7, H9N2 and H10N7, which have resulted in mild infections in a limited number of humans [1,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…T he novel A(H7N9) influenza virus that emerged in China in 2013 (1) continues to cause infections in humans, with approximately 40% mortality (2,3). According to the Food and Agriculture Organization (FAO) website, as of 25 October 2017, 1,622 laboratory-confirmed A(H7N9) cases have been reported, 619 of which have been fatal.…”
mentioning
confidence: 99%
“…We found that memory CD4 T cells specific for H5 HA persisted in subjects vaccinated many years earlier and that these could be recruited into a subsequent immune response to vaccination, enabling a greatly enhanced antibody response to a serologically distinct H5N1-derived virus (20). Should avian influenza viruses continue to pose a threat to humans (54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64), such a prepandemic strategy could enhance vaccine responsiveness in "at risk" subjects and enhance early and potentially protective antibody responses in infected individuals.…”
Section: Discussionmentioning
confidence: 93%